Case Report: New phenotype of late-onset Stüve–Wiedemann syndrome due to a C-terminal variant in the LIFR gene - Melnik, Evgenia; Sharova, Margarita; Kenis, Vladimir; Morgul, Anna; Zabnenkova, Viktoria; Markova, Tatiana (Frontiers in Pediatrics, 2024)
An early diagnosis of Stüve–Wiedemann syndrome is crucial due to its high neonatal lethality and the potential for autonomic dysfunction in children. Herein, we describe a patient with a late-onset, arthrogryposis-like phenotype form of Stüve–Wiedemann syndrome. While most cases result in neonatal complications, our patient only presented with camptodactyly, ulnar deviation of the wrist, and minor facial features at birth, resembling an arthrogryposis-like phenotype. The condition went undiagnosed until adolescence when noticeable gait and posture abnormalities emerged. Clinical and radiological findings confirmed the diagnosis of benign Stüve–Wiedemann syndrome with light autonomic dysregulation. Notably, our patient lacked the typical bent bone features but showed widened metaphyses and thickened femoral necks. Genetic analysis revealed a novel variant in the last exon of the LIFR gene, possibly explaining the mild phenotype. This case expands our understanding of Stüve–Wiedemann syndrome variability, aiding in earlier detection and better medical-genetic counseling.